THE TAXONOMY OF AN “UNSPECIFIED” GROUND IN DISCRIMINATION LAW - Marié McGregor; Wilhelmina Germishuys (Obiter, 2014)
This note will look into cases which have dealt with “unspecified” (or “analogous”) grounds in terms of which direct and indirect unfair discrimination are prohibited by the Constitution of the Republic of South Africa, 1996 (the “Constitution”), the Employment Equity Act 55 of 1998 (“EEA”) and the Labour Relations Act 66 of 1995 (“LRA”). The primary focus is on the classification of “unspecified” grounds in case law by briefly discussing and evaluating the correctness of these decisions. The secondary focus is on the possible expansion of these grounds (with only basic arguments set out).